Impact of desired gift, social value, processed believed, and pleasure donation on loyalty through satisfaction - Yulisetiarini, Diah; Azizah, Yuliatin; Suryaningsih, Ika Barokah; Handriyono; Tobing, Diana Sulianti K (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of desired gifts, social value, processed beliefs, and the pleasure of donation on customer loyalty, with satisfaction serving as a mediating variable. The research aims to understand the motivation and social factors that drive blood donor and consumer retention in charitable and gifting contexts. A quantitative approach was employed, utilizing survey data from 465 donors who have donated more than 10 times continuously from 2018 to 2022 from the Blood Transfusion Unit of Bakorwil V East Java, Indonesia. The analysis method used was Structural Equation Modeling (SEM-PLS) to answer the research hypothesis. The results indicate that social value, processed beliefs, and the pleasure of donation positively influence satisfaction, which in turn enhances loyalty. However, desired gifts have a negative impact on satisfaction, which may hinder the formation of loyalty. This finding suggests that unmet expectations or misalignment of desired gifts can reduce customer or donor satisfaction. The mediating role of satisfaction is significant, reinforcing its importance in the loyalty-building process. The findings provide valuable insights for businesses and nonprofit organizations seeking to strengthen customer and donor relationships. By emphasizing the role of satisfaction in loyalty formation, the study highlights the need for strategic efforts to enhance perceived value and emotional fulfillment in gift-giving and donation experiences. Future research could explore additional psychological and contextual factors influencing loyalty in various cultural and economic settings. The recommendation from the findings is that the implementing agency for blood providers must strengthen social value so that the donor community is encouraged to donate.